Arsenic in Drinking Water Resources in Six Cities Located in the Western Coastal Strip of Libya - Hassan, Tawfik M.; ALamari, Nuri Ibrahim; ALmabsout, Yousef Alsenusi (Jordan Journal of Agricultural Sciences, 2023)
Water used for drinking and food preparation is the most dangerous source of long-term human exposure to arsenic. The study aimed to identify arsenic level in samples of domestic groundwater, public water supply, bottled water, and water from purification shops in five locations along the coastal strip of Libya. The efficiency of removing arsenic in water by reverse osmosis (RO) unit in two water bottling plants was also investigated. Arsenic was analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES). Results show that arsenic in domestic groundwater, public water supply systems, bottled water, and water from purifying shops range respectively: 6.06-70.48, 2.66-22.76, 1.20-11.20, 2.022-9.55 ug/L. The results revealed that 83% of groundwater samples and 5% of bottled water samples exceeded 10ug/l the maximum permissible level in drinking water by Libyan standards. Meanwhile, water samples from purifying shops are below 10ug/l. Public water supply samples from two sites contained arsenic > 10ug/l. The RO unit is able to reduce arsenic in water by 75%, which means that arsenic in unpurified water should not exceed 35 ug/l. The study highly recommends that households who rely on domestic groundwater should install household RO units to be saved from the health risk of chronic arsenic exposure.